Therapeutic Effects of Acoustic Cavitation in the Presence of Gold Nanoparticles on a Colon Tumor Model. (1st March 2013) - Sazgarnia, Ameneh; Shanei, Ahmad; Taheri, Ahmad Reza; Meibodi, Naser Tayyebi; Eshghi, Hossein; Attaran, Neda; Shanei, Mohammad Mahdi
Abstract : Objectives: Acoustic cavitation can be fatal to cells and is used to destroy cancerous tumors. The particles in a liquid decrease the ultrasonic intensity threshold needed for onset of cavitation. Bubble generation from intense pulsed light–irradiated gold nanoparticles was investigated as a means of providing nucleation sites for acoustic cavitation in cancer tissues. Methods: This study was conducted on colon carcinoma tumors in BALB/c mice. The tumor‐bearing mice were randomly divided into 7 groups (each containing 15 mice): (1) control, (2) gold nanoparticles, (3) intense pulsed light irradiation, (4) intense pulsed light + gold nanoparticles, (5) ultrasound alone, (6) ultrasound + gold nanoparticles, and (7) intense pulsed light + ultrasound + gold nanoparticles. In the respective groups, gold nanoparticles were injected into tumors. Intense pulsed light and ultrasound irradiation were performed on the tumors 24 hours after injection. Antitumor effects were estimated by evaluation of the relative tumor volume, doubling time, and 5‐folding time for tumors after treatment. The cumulative survival fraction of the mice and percentage of the lost tissue volume (treated) were also assessed in different groups. Results: A significant difference in the average relative tumor volumes 15 days after treatment was found between the intense pulsed light + ultrasound + gold nanoparticle group and the other groups ( P < .05). The longest doubling and 5‐folding times were observed in the intense pulsed light + ultrasound + gold nanoparticles and ultrasound + gold nanoparticle groups. Conclusions: Acoustic cavitation in the presence of gold nanoparticles and intense pulsed light has been introduced as a new way for improving therapeutic effects on tumors by reducing the relative tumor volume and increasing the cumulative survival fraction.